PERBANDINGAN HASIL BELAJAR BIOLOGI MATERI VIRUS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DAN KONVENSIONAL DI SMA NEGERI 1 UJUNGPADANG KABUPATEN SIMALUNGUN - Desi Desi; Tonggo Sinaga; Risna Wati (Universitas Negeri Medan, 2017)
This study aims to compare the learning outcomes of students who were taught usingcooperative learning model Numbered Head Together (NHT) learning model on Conventional viralmaterial in class X SMA Negeri 1 Ujungpadang Learning Year 2016/2017. The population in this studywere all students of class X SMA Negeri 1 Ujungpadang Learning Year 2015/2016 consisting of 4classes with the number of students as many as 150 people. The sampling method were taken bypurposive sampling (trailer accidentally) the X4 class numbering 37 students as NHT classes and classX1 class of 40 students as conventional. This type of research is an experimental research. The testresults of pretest before being given a different treatment, which is the average value of the pretestNHT class was 38.37 with a standard deviation of 8.84 and average value of pretest Conventionalclass was 37.56 with a standard deviation of 8,31. In the pretest data testing showed that bothclasses of normally distributed data in the two classes and homogeneous. Then after a giventreatment, namely through a different learning model obtained postests with an average yield ofNHT class was 77.20 with a standard deviation of 8.17 and the average yield is 72.5 Conventionalclass with a standard devias 9.81. From the data processing postest found that t = 2.51 and table =1.995 at the level of α = 0.05 so thitung >ttable (2.51 > 0.1995), then H0 is accepted that there is realdifference in statistics on the learning outcomes of students taught using NHT model onConventional viral material in class X SMA Negeri 1 Ujungpadang learning Year 2016/2017.Keywords: NHT, Conventional, Learning Achievement, Virus